PiRNA Biogenesis and Their Role in Human Cancers and Other Diseases: A Narrative Review - Hadi Shirzad (Tehran University of Medical Sciences, 2021)
PIWI-interacting RNAs (piRNAs) with the length of approximately 26-30 nucleotides are a distinct class of small non-coding RNAs that mainly expressed in the animal gonads. Other small RNAs originate from double stranded precursors but piRNAs derive from long single-stranded primary transcripts, which expressed from distinct genomic regions. piRNAs are involved in silencing of mobile elements named transposons and their main role is germline maintenance. Recent studies have opened new insights on biological and clinical significance of piRNAs in various diseases. Abnormal expression of piRNAs is a remarkable feature in many diseases especially human cancers, which emphasize on their important biological role in disease progression. Furthermore, they can be served as biomarkers and therapeutic targets for tumor diagnostics and treatment. In this review, we explained piRNAs characteristics, biogenesis process and functions, discuss new findings about involvement of these elements in various disease and their potential to be used as diagnostic biomarkers.